Is Cannabidiol During Neurodevelopment a Promising Therapy for Schizophrenia and Autism Spectrum Disorders? - Loss, Cássio Morais; Teodoro, Lucas; Rodrigues, Gabriela Doná; Moreira, Lucas Roberto; Peres, Fernanda Fiel; Zuardi, Antonio Waldo; Crippa, José Alexandre; Hallak, Jaime Eduardo Cecilio; Abílio, Vanessa Costhek (Frontiers in Pharmacology, 2021)
Schizophrenia and autism spectrum disorders (ASD) are psychiatric neurodevelopmental disorders that cause high levels of functional disabilities. Also, the currently available therapies for these disorders are limited. Therefore, the search for treatments that could be beneficial for the altered course of the neurodevelopment associated with these disorders is paramount. Preclinical and clinical evidence points to cannabidiol (CBD) as a promising strategy. In this review, we discuss clinical and preclinical studies on schizophrenia and ASD investigating the behavioral, molecular, and functional effects of chronic treatment with CBD (and with cannabidivarin for ASD) during neurodevelopment. In summary, the results point to CBD's beneficial potential for the progression of these disorders supporting further investigations to strengthen its use.